CASE REPORT ON PHENYTOIN-INDUCED IATROGENIC GINGIVAL HYPERPLASIA - GUNTURU, LAKSHMI NARASIMHA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Phenytoin is a diphenylhydantoin which is mostly used in the treatment of epilepsies and arrhythmias. Chronic usage of phenytoin leads to a number of undesirable effects. Most of the adverse effects associated with phenytoin are hirsutism, gingival hyperplasia, osteomalacia, cleft lip, and hypoplastic phalanges. Gingival hyperplasia is an increase in the number of cells or an increase in the size of gingiva is observed due to a defect in collagen metabolism. Here, we report a case of a 20-year-old male patient who was diagnosed with gingival hyperplasia due to the prolonged use of phenytoin for 3 months. The patient’s condition was improved after the withdrawal of phenytoin and other antiepileptic drugs were recommended for his treatment.